2008
DOI: 10.1093/hmg/ddn402
|View full text |Cite
|
Sign up to set email alerts
|

GRM7 variants confer susceptibility to age-related hearing impairment

Abstract: Age-related hearing impairment (ARHI), or presbycusis, is the most prevalent sensory impairment in the elderly. ARHI is a complex disease caused by an interaction between environmental and genetic factors. Here we describe the results of the first whole genome association study for ARHI. The study was performed using 846 cases and 846 controls selected from 3434 individuals collected by eight centers in six European countries. DNA pools for cases and controls were allelotyped on the Affymetrix 500K GeneChip fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
190
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 182 publications
(196 citation statements)
references
References 54 publications
3
190
2
1
Order By: Relevance
“…We have previously reported an association of a common variant in the GRM7 gene, rs11928865, with hearing ability based on a pooling-based GWAS of a European sample set. 9 Therefore, we also genotyped this SNP in the Saami population and analysed these data using the mixed-model approach. This resulted in a P-value of 0.045.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported an association of a common variant in the GRM7 gene, rs11928865, with hearing ability based on a pooling-based GWAS of a European sample set. 9 Therefore, we also genotyped this SNP in the Saami population and analysed these data using the mixed-model approach. This resulted in a P-value of 0.045.…”
Section: Resultsmentioning
confidence: 99%
“…Hitherto, three linkage studies have been performed, [6][7][8] but only one region on chromosome 8q24.13-q24.22 reached genomewide significance. 8 In addition, several association studies based on a candidate gene approach and two genome-wide association studies (GWAS) 8,9 have been conducted. Early candidate gene-based association studies are reviewed by Van Eyken et al 10 Recently, based on a candidate gene approach, we reported associations between ARHI and variants in GRHL2, 11 encoding a transcription factor that is also involved in monogenic hearing loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the GWAS on the Saami, we checked all SNPs with a P-value below 1.0e À4. For the study by Friedman et al, 3 we selected the SNPs that were significant in the GRM7 gene and compared these with our PC1 results. The results are shown in Supplementary Table 2.…”
Section: Common Variant Analysismentioning
confidence: 99%
“…This gene encodes the metabotropic glutamate receptor type7, which is activated through L-glutamate, the primary excitatory neurotransmitter in the cochlear hair cell. 3 A GWAS in 352 samples from the Saami, an isolated population originating from northern Finland, revealed no genome-wide significant associations for ARHI, although the authors noted one SNP immediately downstream of the GRM7 gene among the most significant association signals. 4 In a study on normal hearing function in 3417 persons over age 18, Girotto et al 5 performed a GWAS in 6 isolated European populations using a meta-analysis approach.…”
Section: Introductionmentioning
confidence: 99%